2018
DOI: 10.1021/acs.nanolett.8b03391
|View full text |Cite
|
Sign up to set email alerts
|

Tuning Electroluminescence from a Plasmonic Cavity-Coupled Silicon Light Source

Abstract: The combination of Moore's law and Dennard's scaling rules have constituted the fundamental guidelines for the silicon-based semiconductor industry for decades. Furthermore, the enormous growth of global data volume has pushed the demand for complex and densely packed devices. In recent years, it has become clear that wired interconnects impose increasingly severe speed and power limitations onto integrated circuits as scaling slows toward a halt. To overcome these limitations, there is a clear need for optica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…The Rabi splitting energy, Ω, could be evaluated to be 355 meV, which is larger than the single ZnO/ZnO:Ga superlattice MW-based heterojunction diode. Thus, the enhancement of exciton–photon coupling strength g could be attributed to the reduction of effective mode volume and local field enhancement. ,,,, …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Rabi splitting energy, Ω, could be evaluated to be 355 meV, which is larger than the single ZnO/ZnO:Ga superlattice MW-based heterojunction diode. Thus, the enhancement of exciton–photon coupling strength g could be attributed to the reduction of effective mode volume and local field enhancement. ,,,, …”
Section: Resultsmentioning
confidence: 99%
“…Au plasmons mediated the generation of nonequilibrium hot electrons, and injection into the neighboring superlattice MW can be responsible for the red shift of the EL emissions. 35,52,53 Compared with the waveguiding emission behavior from the single bare superlattice MW, the red-shifted broad emission band can split into more and narrower subbands, resulting in more multiple resonant modes (Figure S8). According to the F−P mode optical cavity formula, the efficient cavity length L could be calculated as 5.2 μm, which is much smaller than the actual width of the bare superlattice MW (∼10 μm).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1−6 These properties have enabled their use in a range of applications such as sensing, solar conversion, photodetection, and synthesis of optically controlled biointerfaces. 7−25 In most cases, the semiconductor wires are interfaced with metal structures that act either as plasmonic materials, 10,11 electrical contacts, 26 or catalysts. 12−24 The ability to precisely locate the metal within the nanostructured substrates is necessary to optimize and control their biological, photocatalytic, and optoelectronic properties.…”
Section: Introductionmentioning
confidence: 99%
“…Silicon nano- and microwire arrays provide versatile architecture with outstanding and tunable optoelectronic properties that can combine light trapping, Mie resonances, waveguiding, and diffractive effects. These properties have enabled their use in a range of applications such as sensing, solar conversion, photodetection, and synthesis of optically controlled biointerfaces. In most cases, the semiconductor wires are interfaced with metal structures that act either as plasmonic materials, , electrical contacts, or catalysts. The ability to precisely locate the metal within the nanostructured substrates is necessary to optimize and control their biological, photocatalytic, and optoelectronic properties. , This is especially true for photo­(electro)­chemical systems that take advantage of the superior photonic properties of nanowire arrays. In these systems, a number of factors can affect the local catalyst activity due to spatially inhomogeneous mass transport, charge recombination, light absorption/scattering, catalyst coverage, and defect distribution. ,,, Recent studies have shown that the deleterious effects of such inhomogeneities can be mitigated by optimizing catalyst location at the semiconductor surface. ,,, However, such investigations are complex and synth...…”
Section: Introductionmentioning
confidence: 99%